REVOLUSI AUDIO DIGITAL: TANTANGAN RADIO DI TENGAH GELOMBANG POPULARITAS PODCAST: Revolusi Audio Digital: Tantangan Radio Di Tengah Gelombang Popularitas Podcast - Kusuma, Adhi; Ghaniyya, Salima Nurul; Saummi, Dea Wulan; Febriyanti, Amelia (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This study analyzes the challenges faced by traditional radio amidst the increasing popularity of podcasts in the digital era. A literature review method is employed to examine changes in consumer preferences regarding audio content consumption and their impact on the existence of traditional radio. The study finds that the flexibility and customization of podcast content, diversity and specialization of topics, high interactivity, and more adaptive monetization models are key factors attracting listeners from traditional radio to podcasts. The research also identifies that traditional radio needs to adopt more flexible digital strategies focusing on content diversification and increased listener engagement. Understanding these trends and dynamics is expected to help the radio industry find new ways to thrive and remain competitive in a constantly evolving media landscape. The findings of this study are expected to provide in-depth insights into how traditional radio can leverage digital technology to maintain relevance and meet the needs of audiences in the future